MOTIVASI BELAJAR PADA MATA PELAJARAN IPAS BERBANTUAN GADGET PESERTA DIDIK KELAS V SDN 1 MOYOKETEN KABUPATEN TULUNGAGUNG - Seftia, Seftia Himatul Husna; Frita, Frita Devi Asriyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study is motivated by the learning of science that is still conventional, where teachers predominantly use printed books and less use of technology, so that learners tend to be passive and less motivated. The use of gadgets is believed to be able to increase learning motivation through access to interesting and interactive information. This study aims to describe the motivation to learn gadget-assisted Science in Class V students of SDN 1 Moyoketen Tulungagung. The study used a descriptive qualitative approach with questionnaire instruments, observations, interviews, and documentation. The results of the analysis of 18 students showed that learning motivation was in the very high category. Impulse and need indicators were dominant in AF, AAZ, AMF, BAA, DA, FAS, FAR, KMF, and LLM, reinforced by observations and interviews in AAZ and others who actively used gadgets. Indicators of interest in the task are shown by AMW, ASP, AHZ and FAR, especially AHZ who are happy to use Google and YouTube. Assiduous indicators are dominant in AAZ, which consistently solves tasks independently. Tenacious indicators facing difficulties appear on AHZ, AAZ, and FAR. Indicators of desire and desirability were successfully seen in AAZ, IR, and KMF, with AAZ being most consistent in achieving learning outcomes.